Propagation criterion of hydraulic fracture in rock based on the rock micro-cracking mechanism - Qingwang Cai; Bingxiang Huang; Xinglong Zhao; Yuekun Xing (International Journal of Mining Science and Technology)
Hydraulic fracture (HF) formed in rock significantly helps with the development of geo-energy and geo-resources. The HF formation condition was challenging to understand, with obscure rock micro-cracking mechanisms being a key factor. The rock micro-cracking mechanism under gradient pore water pressure was analyzed on the scale of mineral particles and it was combined with macroscopic boundary conditions of rock hydraulic fracturing, obtaining the propagation criterion of HF in rock based on the rock micro-cracking mechanism which was verified by experiment. The results show that the disturbed skeleton stress induced by the disturbance of gradient pore water pressure in rock equals the pore water pressure difference. The overall range of the defined mechanical shape factor a/b is around 1, but greater than 0.5. Under the combined influence of pore water pressure differences and macroscopic boundary stresses on the rock micro-cracking, micro-cracks form among rock mineral particles, micro-cracks connect to form micro-hydraulic fracture surfaces, and micro-hydraulic fracture surfaces open to form macro-hydraulic fractures. HF begins to form at the micro-cracking initiation pressure (MCIP), which was tested by keeping the HF tip near the initiation point. The theoretical value of MCIP calculated by the proposed propagation criterion is close to MCIP tested.